Venous Thromboembolic Complications in Patients with Severe and Extremely Severe COVID-19 Infection - Aamer Habeeb Yar Al-Windi (Academic Journal of Clinicians, 2024)
Background: Severe course of the new coronavirus infection (Coronavirus Disease 2019 — COVID-19) is characterized by a violation of the hemostasis system and the development of arterial and venous thrombosis. Objective: To determine the frequency of venous thromboembolic complications (VTEC) in patients with COVID-19 admitted to the intensive care unit (ICU), and to identify predictors of their development. Patients and methods: A retrospective study included 200 patients with severe and extremely severe course of COVID-19 hospitalized in the Intensive care in Al-Shifaa centers for COVID-19. Results: VTE complication was detected in 67 (33.5%) of 200 patients. Venous thrombosis in the system was diagnosed in 63 patients superficial and deep veins, 4 have pulmonary embolism. In 41 (20.5%) patients, VTE was detected on the 1st day of hospitalization in the ICU. In patients with VTEC, the lung lesion area according to computed tomography was greater, artificial ventilation (89.6% and 60.2%, p=0.0001) and vasopressor support (79.1% and 59.4%, p=0.005) were used statistically significantly more often than in patients without VTEC. The survival rate of patients with VTE was statistically significantly lower than without VTE (23 (34.3%) and 76 (57.1%), respectively, p=0.003). In patients with VTEC, one hundred- Statistically significant differences in the values of Willebrand factor antigen (vWF), interleukin 6 (IL-6), antithrombin III (AT III) and protein C compared with patients without VTEC. According to the results of the ROC analysis, AFV of more than 455% (AUC — 0.852 (0.69; 1.00), p=0.008) had a prognostic ability to determine the risk of developing VTEC on the 1st and 7th days; AT III less than 72% and IL-6 more than 256 pg/ml predicted the risk of VTEC on day 1; protein C level at admission less than 81.5% (AUC — 0.79 (0.59—0.99), p=0.042) about- he predicted the development of VTEC by the 7th day. Conclusion: The frequency of VTEC diagnosed in the ICU was 33.5%. In 60% of all cases, VTEC developed outside the ICU. The determination of AFB activity, AT III activity, IL-6 concentration and protein C activity enables the prediction of VTE progression in individuals with severe and extremely severe conditions. COVID-19.